Perbedaan Tekanan Darah Sebelum Dan Sesudah Penerapan Diet Dietary Approaches To Stop Hypertension (DASH) Pada Lansia Hipertensi - Yudha, Pramitha; Subekti, Imam; Bachtiar, Arief; Wiyono, Joko; Widodo, Dyah (Jurnal Keperawatan Florence Nightingale, 2025)
Hypertension is a non-communicable disease that is a leading cause of morbidity and mortality, especially in the elderly. Diet is a key factor in controlling blood pressure, yet many older adults still do not follow an appropriate diet, including the Dietary Approaches to Stop Hypertension (DASH) diet. This dietary inadequacy contributes to the difficulty of controlling blood pressure in elderly with hypertension. The Objective to determine the difference in blood pressure before and after the implementation of the DASH diet in elderly with hypertension. This study used a quasi-experimental design with a non-equivalent control group approach, involving 30 respondents who were divided into treatment and control groups through total sampling. Respondents were selected based on the criteria of elderly with pre-hypertension, grade 1, and grade 2 hypertension. The independent variable was the DASH diet, while the dependent variable was changes in blood pressure. Data analysis included univariate analysis for respondent characteristics and comparison of blood pressure, as well as bivariate analysis using the Paired T-Test and Mann Whitney Test.The Paired T-Test in the control group was 0.719 for systolic and 0.546 for diastolic. Paired T-Test test in the treatment group 0.000 in systolic and 0.002 in diastolic. Mann-Whitney Test in the control and treatment groups 0.027 in systolic and 0.032 in diastolic. There was a significant difference between systolic and diastolic blood pressure before and after implementing the DASH diet in elderly people with hypertension. The DASH diet is effective as a non-pharmacological intervention in controlling blood pressure. The results of this study recommend that nurses play an active role in providing education, support, and monitoring the implementation of the DASH diet as part of comprehensive nursing care for elderly people with hypertension.